Метаболізм як напрям розвитку архітектури у післявоєнній відбудові - Кузьо, Софія; Петришин, Галина; Kuzio, Sophia; Petryshyn, Halyna (Видавництво Львівської політехніки, 2023)
Після другої світової креативне мислення архітекторів Японії вилилось в метаболізм - новий архітектурний напрям з ідеологією, що відповідає культурі та побуту держави. Метаболізм поєднав ідеї про архітектурні мегаструктури з ідеями органічного росту. У 1960 р. у Токіо архітектори-метаболісти, представили свій маніфест під назвою "Пропозиція нового урбанізму". Метаболісти вважали, що архітектура повинна підкорятись законам природи і дотримуватись циклу життя і концепції смерті. Їхні проекти базувалися на розділенні будівельних компонентів з різним терміном служби. Вони проектували її з метою забезпечення максимальних адаптивності і гнучкості. Сьогодні метаболізм має зв’язок із стійкістю міст у світлі техніко-матеріальної парадигми, запропонованої міською екологією.

After World War II, the creative thinking of architects in Japan resulted in metabolism, a new architectural direction with an ideology that corresponded to the culture and lifestyle of the state. The metabolism theory was based on the principle of individual development of a living organism (ontogenesis) and coevolution. Metabolism combined ideas about architectural megastructures with ideas of organic growth. In 1960 in Tokyo, Metabolist architects presented their manifesto "Metabolism 1960: Proposals for a New Urbanism", which proposed a vision of the city in constant change and growth. Sustainable Metabolism Architecture, the idea of separating building components and grouping them based on their lifespan, may be an effective resource conservation solution today. Also, the methods and means of metabolic architecture are appropriate for supplementing the destroyed housing stock of Ukraine. Bold planning decisions for the development of "cities on ruins" allow us to rethink the meaning of megastructures and the types of their filling. Numerous studies have been devoted to the architecture of metabolism, the summation of which is a critical photo album by Rem Koolhaas, where he reassessed this phenomenon from the distance of time (Koolhaas and Obrist 2011). In domestic practice, the metabolism ideas were combined with Soviet modernism, and the main concepts were introduced into the educational process (Cherkes Linda, 2011; Kryvoruchko, 2011). Modern researchers believe that disasters force us to reconsider our views on architecture and make decisions. What architects can do for people who have lost everything (Tamari, 2014). Also, modern studies link the metabolism in cities with the goals of sustainable development (Chen F. & Chen Y. 2022) and testify to a new understanding of the metabolism of the city as a whole (Céspedes Restrepo & Morales-Pinzón, 2018). The purpose of the article is to consider the phenomenon of architectural and urban metabolism and their connection with the growth, expansion, and reconstruction of cities; identify in the course of metabolism of approaches and means useful for the reconstruction of destroyed cities; reveal the formation of iconic objects by Japan's leading metabolic architects.
Metabolism as a direction of architecture development in post-war reconstruction
Keywords: метаболізм; капсульна архітектура; післявоєнна відбудова; реконструкція; місто майбутнього; metabolism; capsule architecture; post-war reconstruction; reconstruction; city of the future; 72.03(520)